Extent and Purpose of Adopting ICT For Agribusiness Development: The Case of Sampled-Firms in East Java - Sudaryanto Sudaryanto; Soekartawi Soekartawi (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2009)
This article is a part of the first-author PhD-dissertation entitled ‘Factors Influencing ICT Adoption in EastJava Agribusiness: Individual and Organisational Approaches’. The main objective of presenting this article issharing information related to investigation of ICT adoption done by samples who are asked to respond to amultiple response questions.ICT adoption ladder model is used for the analysis. The samples are grouped into four level of adoption---lowest to highest level), namely (i) ICT- Conventional, consists of fixed line phone, facsimile, and mobile phone,(ii) ICT- Computer, consists of stand alone computer with access to the internet via internet cafes, (iii) ICTInternet,consists of use of the internet for email and using a web browser, and (iv) ICT-E-business, consists ofusing the internet for advertising, online business and virtual organisation activities.About 178 sampled firms (farmers) in four regencies (Jember, Banyuwangi, Malang, Sidoarjo) wereinterviewed in 2006. The respondents were given their opportunity to respond to multiple options on the purposefor adopting ICT. Five options of ICT use were proposed: (i) ICT for communication among employees, (ii) ICTfor communication between companies and distributors, (iii) ICT for marketing and sales, (iv) ICT for searchingcompany’s resources, and (v) ICT for other purposes.Results of the analysis show that all samples in group 1 (100%) adopted the lowest level of ICT. Group 2, 3,and 4, respectively, adopted 75.3%; 44.9%; and 10.7%. This indicates the default automatic adoption level ofwhich all businesses operate at the minimum. The ladder shows that the higher the level, the smaller thepercentages of sampled firms. This means that as ICT technology becomes more sophisticated, fewer sampledfirms opt to adopt the higher levels on the ICT ladder. Also, firms at the higher levels still use ICT technologyfrom the lower levels. In other words, the existence of adopter advanced levels of ICT does not mean a reductionof use at the lower levels. Some businesses maintain their existing ICT adoption levels and are not interested inimprovement by moving to the more sophisticated levels of ICT, due to considerations which will be investigatedin this research.The results also show that general purposes of using ICT at the very basic level of the ladder needs to beinvestigated in order to draw a picture of the benefit of adopting ICT.Keywords: ICT adoption, agribusiness, Indonesia